Synthesis and reactivity of cationic iridium aminocarbenes derived from terminal alkynes and 2-aminopyridines - Kumaran, Elumalai (2014)
The reaction of a terminal alkyne (RCCH) and 2- aminopyridine (R′C5NH3NH2) with the dinuclear species [Cp*IrCl2]2 afforded the cationic aminocarbene derivatives Cp*Ir(Cl)[ C- (CH2R)NHC5NH3R′] via a hydroamination and a ligand substitution. The reaction pathway has been examined through computational studies.